Clinical and histopathologic manifestations of solid organ transplantation‐associated graft‐versus‐host disease involving the skin: A single‐center retrospective study. (19th August 2018) - Kim, Grace Y.; Schmelkin, Leah A.; Davis, Mark D.; El‐Azhary, Rokea A.; Wieland, Carilyn N.; Leise, Michael D.; Meves, Alexander; Lehman, Julia S.
Abstract : Background: Graft‐versus‐host disease (GVHD) following solid organ transplantation (SOT) is extremely rare and infrequently described in the dermatologic literature. Methods: We performed a retrospective clinicopathologic review of our institution's experience with patients diagnosed with SOT‐associated GVHD (SOT GVHD) (May 1, 1996 to September 1, 2017). Results: Of nine patients with SOT GVHD, seven had undergone liver transplantation, while two had undergone lung transplantation. All presented initially with a skin eruption, which developed an average of 63 days (range: 11‐162 days) post transplant. The average time to diagnosis following the onset of the skin eruption was 12 days (range: 0‐54 days). Diagnosis was often delayed because of a competing diagnosis of drug reaction. Frequent skin findings included pruritic erythematous to violaceous macules and papules with desquamation. Histopathology showed vacuolar interface dermatitis in 12 of 15 cases (80.0%). Of the 11 specimens in which a hair follicle was present for evaluation, vacuolar interface changes around the hair follicle were present in eight (72.7%) cases. Seven patients (77.8%) died from complications during the follow‐up period. Conclusions: SOT GVHD presents initially with skin involvement, is associated with vacuolar interface changes on skin biopsy, and is associated with a high mortality rate. Clinicopathologic correlation is required for accurate diagnosis.